Implementation of Educational Psychology in Improving the Quality of Learning at Elementary School 3 Klaten - Purwanto, Purwanto; Nur Wangid, Muhammad (Journal of World Science, 2022)
Introduction: This “research is motivated by the problems of principals and teachers in applying educational psychology at Elementary School 3 Klaten to improve the quality of learning. In this case, many classroom teachers experience obstacles and difficulties implementing psychological education. Researchers observed and analyzed the implementation of educational psychology by Elementary School 3 Klaten teachers in improving the quality of learning. The objectives of this study include: knowing how teachers implement educational psychology, the obstacles experienced by teachers in implementing educational psychology, and reviewing teacher efforts in overcoming these obstacles to improve the quality of learning. Method: This study uses a descriptive qualitative approach. The research was conducted at Elementary School 3 Klaten for the academic year 2022/2023. This study analyses teachers implementing educational psychology and supervision carried out by school principals to improve the quality of learning. Result: Based on the analysis of observational data, documentation, and interviews, it shows that teachers at Elementary School 3 Klaten have implemented educational psychology in learning to improve the quality of learning with support and supervision carried out by the school principal. Conclusion: The implementation of educational psychology at Elementary School 3 Klaten is applied by teachers in various ways to improve the quality of learning, including using multiple methods in education, tools, and media, prioritizing interaction with students, providing guidance, motivation, attention, direction, and fair assessment.